Psychiatric disorders and adherence to antiretroviral therapy among a population of HIV-infected adults in Nigeria (2016)
Psychiatric disorders are common among HIV patients in Nigeria. Adherence is necessary to optimize the outcome of antiretroviral therapy. In this study, we aimed to identify associations between antiretroviral adherence measured by 1-week and 1-month self-reported missed doses, and psychiatric illness in a cohort previously assessed for psychiatric disorders using the Composite International Diagnostic instrument (CIDI). The study participants comprised 151 adults with major depression, anxiety or suicidal symptoms, and 302 matched-control participants. Two controls were randomly selected for each case within the same gender and education stratum. We compared participants with psychiatric disorders (WPDs) and without psychiatric disorders (NPDs) on selected demographic and clinical variables, in addition to adherence. Participants with 1 or more missed doses in the preceding month had twice the odds of having a major depressive episode as those with no missed doses during this period (OR 2.22, 95% CI 1.03, 4.79). This association remained significant after adjusting for selected risk factors. There was no statistically significant difference between WPD and NPD groups on either 1-week or 1-month adherence, or on age, marital status, occupational class, HIV viral load at enrollment or current CD4. Among Nigerian adults with HIV, suboptimal antiretroviral adherence is associated with, and could be a Corresponding author: Olurotimi Adejumo, Department of Psychiatry, University College Hospital, PMB 5116, Ibadan, Nigeria, Phone: +2348033778540, +13122167417, radejumo@yahoo.com. HHS Public Access Author manuscript Int J STD AIDS. Author manuscript; available in PMC 2016 October 01. Published in final edited form as: Int J STD AIDS. 2016 October ; 27(11): 938–949. doi:10.1177/0956462415600582. Author Manuscript Author Manuscript Author Manuscript Author Manuscript pointer to depression. Routine self-report adherence assessments may have potential utility for identifying individuals at risk among this population.